Composite copper layer and preparation method thereof
By adjusting the volume percentage of the double-crystal copper grains in the composite copper layer and changing the starting temperature of grain growth, the problem of unstable copper film grain growth is solved, and the stable state and expectation of the composite copper layer before the process is achieved Effect.
Patent Information
- Application Number
- CN202410843817.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-27
- Publication Date
- 2024-12-31
AI Technical Summary
The grain growth starting temperature of existing copper films is difficult to control, resulting in unstable process conditions and affecting the application of copper in the fields of electricity and chemical industry.
By adjusting the volume percentage of the double-crystal copper grains in the composite copper layer, changing the starting temperature of grain growth, so that the composite copper layer is in a stable state with substantially no grain growth changes when it is lower than this temperature, using electrolytic deposition technology Deposit a composite copper layer of double-crystalline copper and nano-copper grains.
Effective control of the starting temperature of the grain growth of the composite copper layer is achieved, ensuring stable state before the process, and improving the application effect of the copper-copper metal bonding process.
Smart Images

Figure CN119221052A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composite copper layer and a preparation method thereof, and more particularly to a composite copper layer and a preparation method thereof, wherein the starting temperature of grain growth change of the composite copper layer is determined according to the volume ratio of twin copper grains in the composite copper layer. Background Art
[0002] Copper is often used in the fields of electricity, chemical industry, aerospace, etc. due to its good thermal conductivity, electrical conductivity, corrosion resistance and plasticity, and plays a vital role in human life and work.
[0003] Since coarse-crystal pure copper has high deformation capacity but low strength, in order to improve the performance of copper, it is usually possible to add trace elements to make alloys to increase its hardness and strength, but this will cause a significant decrease in the conductivity of copper, thereby reducing the application of copper in electricity. Furthermore, the addition of a small amount of iron and nickel elements will affect the magnetism of copper, which is not conducive to its application in the manufacture of magnetically sensitive devices, such as compasses.
[0004] In addition, the grain growth starting temperature of the copper film significantly affects the application of the copper film in various fields (such as copper-copper metal bonding process). In particular, when the grain growth starting temperature of the copper film is lower than the process temperature, the copper film may show an unstable state of grain growth before the process starts, making it difficult to control the process conditions, thereby causing the process effect to be less than expected. Therefore, how to effectively control the grain growth starting temperature of the copper film is one of the important issues for the application of the copper film in various fields. Summary of the invention
[0005] An object of the present invention is to provide a composite copper layer and a preparation method thereof, which can effectively control the grain growth starting temperature of the composite copper layer according to process requirements, so that the composite copper layer has a relatively stable state before the process is carried out, thereby achieving effective process condition control and expected process effects.
[0006] Another object of the present invention is to provide a composite copper layer and a preparation method thereof, which determines the starting temperature of grain growth by adjusting the volume percentage of twin copper grains in the composite copper layer, so that the composite copper layer is in a stable state with substantially no grain growth change at a temperature below the starting temperature, which is helpful for the application of copper-copper metal bonding process.
[0007] In one embodiment, the present invention provides a composite copper layer, which includes twinned copper grains and nano-copper grains. The twinned copper grains and the nano-copper grains are intermixed so that the composite copper layer has a starting temperature. The composite copper layer is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature, wherein the starting temperature of the composite copper layer is determined based on the volume percentage of the twinned copper grains in the composite copper layer.
[0008] In one embodiment, the volume percentage of the composite copper layer occupied by the twinned copper grains is less than 1%, and the starting temperature is less than 50 degrees Celsius.
[0009] In one embodiment, when the volume percentage of the composite copper layer occupied by the twinned copper grains is in the range of 1% to 60%, the starting temperature increases with the increase of the volume percentage.
[0010] In one embodiment, the volume percentage of the composite copper layer occupied by the twinned copper grains is 10-20%, and the starting temperature is less than 100 degrees Celsius.
[0011] In one embodiment, the volume percentage of the composite copper layer occupied by the twinned copper grains is 30-45%, and the starting temperature is less than 200 degrees Celsius.
[0012] In one embodiment, the composite copper layer is applied in a copper-copper metal bonding process.
[0013] In another embodiment, the present invention provides a method for preparing a composite copper layer, comprising: using an electrolyte comprising a copper salt, an acid, and a water-soluble or alcohol-soluble organic additive to deposit a composite copper layer comprising twinned copper grains and nano-copper grains on the surface of a cathode by an electrolytic deposition technique, wherein the twinned copper grains and the nano-copper grains are intermixed so that the composite copper layer has a starting temperature, and the composite copper layer is in a stable state with substantially no grain growth change at a temperature below the starting temperature, wherein the starting temperature of the composite copper layer is changed by adjusting the volume percentage of the twinned copper grains in the composite copper layer.
[0014] In one embodiment, the volume percentage of the composite copper layer occupied by the twinned copper grains is adjusted by adjusting the content of the water-soluble or alcohol-soluble organic additive.
[0015] In one embodiment, the volume percentage of the composite copper layer occupied by the twinned copper grains is adjusted to be less than 1%, so that the starting temperature is less than 50 degrees Celsius.
[0016] In one embodiment, the volume percentage of the composite copper layer occupied by the twinned copper grains is adjusted to a range of 1% to 60%, such that the starting temperature increases with an increase in the volume percentage.
[0017] In one embodiment, the volume percentage of the twinned copper grains in the composite copper layer is adjusted to 10-20%, so that the starting temperature is less than 100 degrees Celsius.
[0018] In one embodiment, the volume percentage of the twinned copper grains in the composite copper layer is adjusted to 30-45%, so that the starting temperature is less than 200 degrees Celsius.
[0019] In one embodiment, the electrolysis conditions include a current density of 20-100 mA / cm 2, the cell voltage is 0.2~3 V, and the distance between the cathode and the anode is 10~300 mm. The acid in the electrolyte is sulfuric acid, hydrochloric acid, phosphoric acid, methanesulfonic acid, sulfonic acid or a mixture thereof, the copper salt contained in the electrolyte is copper sulfate, and the copper sulfate concentration of the electrolyte is above 0.3 mol / L, and the water-soluble or alcohol-soluble organic additive in the electrolyte is a cellulose organic additive, and its molecular weight is between 500~100000 and includes cellulose, hemicellulose, carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, ethyl cellulose, and propyl cellulose.
[0020] Compared with the prior art, the composite copper layer and preparation method thereof of the present invention determines (changes) the starting temperature of grain growth by adjusting the volume percentage of the twin copper grains in the composite copper layer, so that the composite copper layer is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature. The starting temperature of grain growth of the composite copper layer can be effectively controlled according to process requirements, so that the composite copper layer has a relatively stable state before the process is carried out, thereby achieving effective process control and expected process effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the relationship between the annealing temperature and resistance change of the composite copper layer of each embodiment of the present invention.
[0022] Figures 2 to 4 Schematic diagrams showing the structural changes of the composite copper layers of different embodiments of the present invention at different annealing temperatures.
[0023] Figure 5 Schematic diagram of an electrolytic deposition device used in a method for preparing a composite copper layer according to an embodiment of the present invention.
[0024] Description of main component symbols:
[0025] 1 Electrolytic deposition device
[0026] 10. Electrolyzer
[0027] 20 Cathode
[0028] 22 Surface
[0029] 30 Anode
[0030] 40 Current supply source
[0031] 50 electrolyte
[0032] 100 Twinned Copper Grains
[0033] 200 nanometer copper grains
[0034] 300 growth grains
[0035] 501, 502, 503 composite copper layer DETAILED DESCRIPTION
[0036] In the accompanying drawings, for the sake of clarity, the thickness of layers, films, panels, regions, etc. is magnified. Throughout the specification, the same reference numerals represent the same elements. It should be understood that when an element such as a layer, film, region or substrate is referred to as being "on" or "connected to" another element, it can be directly on or connected to another element, or an intermediate element can also exist. On the contrary, when an element is referred to as being "directly on" or "directly connected to" another element, there is no intermediate element. As used herein, "connection" can refer to physical and / or electrical connection. Furthermore, "electrical connection" or "coupling" can be other elements between two elements.
[0037] In addition, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element, as shown in the figures. It should be understood that relative terms are intended to include different orientations of the device in addition to the orientation shown in the figures. For example, if the device in one figure is turned over, the element described as being on the "lower" side of the other elements will be oriented on the "upper" side of the other elements. Therefore, the exemplary term "lower" can include both "lower" and "upper" orientations, depending on the specific orientation of the figure. Similarly, if the device in one figure is turned over, the element described as being "below" or "below" other elements will be oriented as being "above" other elements. Therefore, the exemplary term "below" or "below" can include both above and below orientations.
[0038] As used herein, "about", "approximately", or "substantially" includes the stated value and the average value within an acceptable deviation range of the particular value determined by one of ordinary skill in the art, taking into account the measurement in question and the particular amount of error associated with the measurement (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the stated value, or within ±30%, ±20%, ±10%, ±5%. Furthermore, as used herein, "about", "approximately", or "substantially" can select a more acceptable deviation range or standard deviation depending on the optical property, chemical property, physical property or other property, and can apply to all properties without a single standard deviation.
[0039] Figure 1The figure is a schematic diagram of the relationship between the annealing temperature and the resistance change of the composite copper layer of each embodiment of the present invention, wherein the horizontal axis represents temperature (°C) and the vertical axis represents resistance change (R / R0). R0 represents the reference resistance of the composite copper layer obtained at room temperature, and R represents the measured resistance of the composite copper layer obtained at different temperatures. Furthermore, the change of the grain will affect the change of resistance. For example, when the resistance value starts to decrease, it means that the grain begins to grow and become larger. Therefore, by observing the resistance change, the starting temperature of the grain growth corresponding to the composite copper layer of each embodiment can be obtained. Furthermore, in the embodiment, "the resistance value starts to decrease" can be represented by the resistance change (R / R0) reaching a preset value and starting to decrease. The preset value is preferably in the range of 1 to 0.95, for example. Before the resistance change does not reach the preset value, it means that the composite copper layer is in a stable state with substantially no grain growth change. Even if there may be some slight grain growth changes, the growth changes are negligible or caused by measurement errors. Therefore, the starting temperature of the grain growth corresponding to the composite copper layer is the temperature at which the corresponding resistance change (for example, R / R0) reaches the preset value. That is, the composite copper layer at a temperature lower than the starting temperature can be regarded as a stable state with substantially no grain growth change.
[0040] like Figure 1 As shown, in the composite copper layer of Example 1, the volume percentage of the composite copper layer occupied by the twin copper grains is less than 1%, and the starting temperature of the grain growth of the composite copper layer is less than 50 degrees Celsius, for example, about 30 degrees Celsius. In other words, the composite copper layer of Example 1 has a very large volume percentage of nano copper grains (for example, a volume percentage greater than 99%), and is therefore relatively unstable at high temperatures, and the temperature effect must be considered under high temperature processes. In the composite copper layer of Example 2, the volume percentage of the composite copper layer occupied by the twin copper grains is 10-20%, and the starting temperature of the grain growth of the composite copper layer is less than 100 degrees Celsius. In Example 2, as the volume percentage of the composite copper layer occupied by the twin copper grains increases, the starting temperature of the grain growth of the composite copper layer of Example 2 is greater than or equal to the starting temperature of the grain growth of the composite copper layer of Example 1 (for example, greater than or equal to 50 degrees Celsius). In the composite copper layer of Example 3, the volume percentage of the composite copper layer occupied by the twinned copper grains is 30-45%, and the starting temperature of the grain growth of the composite copper layer is less than 200 degrees Celsius. As the volume percentage of the composite copper layer occupied by the twinned copper grains increases, the starting temperature of the grain growth of the composite copper layer of Example 3 is greater than or equal to the starting temperature of the grain growth of the composite copper layer of Example 2 (for example, greater than or equal to 100 degrees Celsius). In the composite copper layer of Example 4, the volume percentage of the composite copper layer occupied by the twinned copper grains is greater than 60%, and the starting temperature of the grain growth of the composite copper layer is greater than (or equal to) 400 degrees Celsius.
[0041] Depend on Figure 1It can be seen that by adjusting the volume percentage of the twin copper grains occupying the composite copper layer, the starting temperature of the grain growth of the composite copper layer can be adjusted to facilitate the composite copper layer to be applied to the copper-copper metal bonding process. Specifically, in the range of 1% to 60% of the volume percentage of the twin copper grains occupying the composite copper layer, the starting temperature increases with the increase of the volume percentage of the twin copper grains. Therefore, according to the process requirements, a composite copper layer with an appropriate volume percentage of the twin copper grains occupying the composite copper layer can be applied, so that the composite copper layer has a better starting temperature that matches the process requirements, so as to help achieve process control and expected process effects. Furthermore, as shown in Example 4, when the volume percentage of the twin copper grains occupying the composite copper layer is greater than 60%, the resistance of the composite copper layer does not change much with the increase in temperature, which means that the composite copper layer is quite stable even at a high temperature of 400 degrees Celsius, and is suitable for high temperature processes.
[0042] Figures 2 to 4 Schematic diagram showing the structural changes of the composite copper layer of different embodiments of the present invention at different annealing temperatures, wherein Figure 2 In the embodiment, since the volume percentage of the twinned copper grains in the composite copper layer 501 is less than 1%, Figure 2 The twinned copper grains are not indicated, only the nano copper grains 200 are indicated. Figure 2 As shown, corresponding to Figure 1 In the first embodiment, the composite copper layer 501 is a structure in which the volume percentage of the twinned copper grains in the composite copper layer 501 is less than 1%, and the starting temperature is less than 50 degrees Celsius. Specifically, since the starting temperature of the composite copper layer 501 is less than 50 degrees Celsius (e.g., about 30 degrees Celsius), the composite copper layer 501 can be self-annealed within a few hours, so that the grains grow into the growing grains 300. Figure 3 As shown, corresponding to Figure 1 In Example 3, the composite copper layer 502 is represented as a structure in which the volume percentage of the twin copper grains 100 in the composite copper layer 502 is 30-45%, and its starting temperature is less than 200 degrees Celsius. Specifically, since the starting temperature of the composite copper layer 502 is less than 200 degrees Celsius and greater than 100 degrees Celsius, the composite copper layer 502 is in a stable state with substantially no grain growth change when annealed at 100 degrees Celsius. However, when annealed at 200 degrees Celsius, the grains of the composite copper layer 502 grow (i.e., the twin copper grains 100 and / or nano copper grains 200 are bonded to each other) to grow grains 300. Figure 4 As shown, corresponding to Figure 1In Example 4, the composite copper layer 503 is represented as a structure in which the volume percentage of the twinned copper grains 100 in the composite copper layer 503 is greater than 60%, and its starting temperature is greater than 400 degrees Celsius. Specifically, since the starting temperature of the composite copper layer 503 is greater than 400 degrees Celsius, the composite copper layer 503 is in a stable state with substantially no grain growth change when annealing is performed at 200 degrees Celsius, and is still in a stable state with substantially no grain growth change when annealing is performed at 400 degrees Celsius.
[0043] In the above embodiments, the composite copper layer (eg Figures 2 to 4 The composite copper layer 501, 502 or 503) includes twinned copper grains 100 and nano copper grains 200. The twinned copper grains 100 and nano copper grains 200 are intermixed so that the composite copper layer 501, 502 or 503 has a corresponding starting temperature, and the composite copper layer 501, 502 or 503 is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature. The starting temperature of the composite copper layer 501, 502 or 503 can be determined (changed) according to the volume percentage of the twinned copper grains 100 in the composite copper layer 501, 502 or 503.
[0044] In one embodiment, the preparation method of the composite copper layer of the present invention comprises: using an electrolyte containing a copper salt, an acid and a water-soluble or alcohol-soluble organic additive to deposit a composite copper layer containing twinned copper grains and nano copper grains on the surface of a cathode by an electrolytic deposition technique. The twinned copper grains and the nano copper grains are intermixed so that the composite copper layer has a starting temperature, and the composite copper layer is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature, wherein the starting temperature of the composite copper layer is changed by adjusting the volume percentage of the twinned copper grains in the composite copper layer.
[0045] Figure 5 Schematic diagram of an electrolytic deposition device used in a method for preparing a composite copper layer according to an embodiment of the present invention. Figure 5As shown, the electrolytic deposition device 1 includes an electrolytic cell 10, a cathode 20, an anode 30 and a current supply source 40. The cathode 20 and the anode 30 are separated and arranged in the electrolytic cell 10, and the current supply source 40 is electrically connected to the cathode 20 and the anode 30 to supply the power required for the reaction. In one embodiment, the anode 30 is preferably a copper plate with a purity higher than 99.99%, but is not limited thereto. In other embodiments, the anode 30 can be other metal materials, such as phosphor copper, and other insoluble anodes, such as titanium metal plates and titanium metal plates coated with iridium dioxide. The surface 22 of the cathode 20 is preferably a suitable surface on which a copper film is to be deposited, such as a semiconductor surface in a semiconductor process (such as the surface of a silicon wafer), a metal material surface (such as the surface of a titanium sheet, an iron sheet, a nickel sheet or a pure copper sheet), or a metal layer or a seed layer on a non-metallic substrate (such as a glass substrate, a quartz substrate, a plastic substrate or a printed circuit board, etc.), or a surface of a substrate having a crystal direction. The electrolyte 50 used in the present invention is injected into the electrolytic cell 10 to contact the cathode 20 and the anode 30 .
[0046] In one embodiment, the acid in the electrolyte 50 may be sulfuric acid, hydrochloric acid, phosphoric acid, methanesulfonic acid, sulfonic acid or a mixture thereof. The copper salt in the electrolyte 50 is preferably copper sulfate, and the copper sulfate concentration in the electrolyte 50 is about 0.3 mol / L or more. The water-soluble or alcohol-soluble organic additive in the electrolyte 50 may be a cellulose-based organic additive, and its molecular weight is preferably between 500 and 100,000 and may include cellulose, hemicellulose, carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, ethyl cellulose, and propyl cellulose.
[0047] The content of the cellulose organic additive is preferably 0.01 g / L or more, more preferably 0.01 g / L to 1 g / L, but not limited thereto. According to actual needs, the preparation method of the present invention can adjust the volume percentage of the twinned copper grains occupying the composite copper layer by adjusting the content of the water-soluble or alcohol-soluble organic additive, so as to make the composite copper layer have a corresponding grain growth starting temperature. For example, the content of the cellulose organic additive can also be 1 g / L or more.
[0048] Furthermore, the conditions for the electrolytic deposition may be, for example, a current density of 20 to 100 mA / cm 2 , the cell voltage is 0.2-3 V, the distance between the cathode and the anode is 10-300 mm, and the electrolyte temperature is 15-30 ° C. For example, when an insoluble anode is used, a higher cell voltage can be used. A composite copper layer comprising twinned copper grains and nano-copper grains is deposited on the surface of the cathode by electrolytic deposition technology, wherein the volume percentage of the twinned copper grains in the composite copper layer is preferably adjusted to a range of 1% to 60%, so that the starting temperature increases with the increase in the volume percentage of the twinned copper grains.
[0049] Preparation of Examples 1 to 4
[0050] In the preparation of Example 1, the copper sulfate content of the electrolyte 50 is, for example, 60 to 80 grams of copper sulfate per liter (i.e., 60~80g CuSO4 / L). The electrolyte 50 may also contain an inhibitor and an accelerator, for example, the content of the inhibitor is 30 ml / L, and the content of the accelerator is 6 ml / L, wherein the inhibitor contains a water-soluble or alcohol-soluble organic additive that is a cellulose organic additive, and its content is 0.3 g / L. As a result, the volume percentage of the twinned copper grains in the formed composite copper layer occupied by the composite copper layer is less than 1%, so that the starting temperature of the grain growth of the composite copper layer is less than 50 degrees Celsius. In addition, in this embodiment, on the surface of the composite copper layer, the surface percentage of the twinned copper grains occupied by the composite copper layer is, for example, less than 1%. It should be noted here that the inhibitor is used to inhibit the growth of copper grains during the electroplating process to achieve a suitable crystal growth rate and a specific crystal structure, such as a need for filling holes, that is, an inhibitor is needed; and the accelerator is used to accelerate the growth of copper grains, which can greatly increase the nano copper grains, such as the accelerator can be used to increase the flatness of the copper surface. The whole system can be operated under the deployment of both inhibitors and accelerators.
[0051] In the preparation of Example 2, the copper sulfate content of the electrolyte 50 is, for example, 60 to 80 grams of copper sulfate per liter (i.e., 60~80g Cu SO4 / L). The electrolyte 50 may also contain an inhibitor and an accelerator, for example, the content of the inhibitor is 30 ml / L, and the content of the accelerator is 3 ml / L, wherein the inhibitor contains a water-soluble or alcohol-soluble organic additive that is a cellulose organic additive, and its content is 0.5 g / L. As a result, the volume percentage of the twinned copper grains in the formed composite copper layer is 10~20%, so that the starting temperature of the grain growth of the composite copper layer is less than 100 degrees Celsius and greater than or equal to 50 degrees Celsius. In addition, in this embodiment, on the surface of the composite copper layer, the twinned copper grains occupy a surface percentage of the composite copper layer of, for example, 5~10%.
[0052] In the preparation of Example 3, the copper sulfate content of the electrolyte 50 is, for example, 60 to 80 grams of copper sulfate per liter (i.e., 60~80g Cu SO4 / L). The electrolyte 50 may also contain an inhibitor, for example, the content of the inhibitor is 30 ml / L, wherein the inhibitor contains a water-soluble or alcohol-soluble organic additive that is a cellulose organic additive, and its content is 0.5 g / L. As a result, the volume percentage of the composite copper layer occupied by the twinned copper grains in the formed composite copper layer is 30~45%, so that the starting temperature of the grain growth of the composite copper layer is less than 200 degrees Celsius and greater than or equal to 100 degrees Celsius. In addition, in this embodiment, on the surface of the composite copper layer, the twinned copper grains occupy a surface percentage of the composite copper layer of, for example, 20~30%. It should be noted here that the accelerator essentially affects the growth of twinned copper. To grow a certain proportion or a high proportion of twinned copper, it is not necessary to add an accelerator, and at the same time, obvious twinned copper grains begin to appear inside the copper structure. Therefore, in this embodiment 3, although the amount of inhibitor used and the content of water-soluble or alcohol-soluble organic additives are the same as those in embodiment 2, since no accelerator is used, the volume percentage of the twinned copper grains in the formed composite copper layer occupied by the composite copper layer is relatively increased.
[0053] In the preparation of Example 4, the copper sulfate content of the electrolyte 50 is, for example, 60 grams of copper sulfate per liter (i.e., 60g Cu SO4 / L). The electrolyte 50 may also contain an inhibitor, for example, the inhibitor content is 30 ml / L, wherein the inhibitor contains a water-soluble or alcohol-soluble organic additive that is a cellulose organic additive, and its content is 0.6 g / L. As a result, the volume percentage of the composite copper layer occupied by the twinned copper grains in the formed composite copper layer is greater than 60%, so that the grain growth starting temperature of the composite copper layer is greater than (or equal to) 400 degrees Celsius. In addition, in this embodiment, on the surface of the composite copper layer, the twinned copper grains 100 occupy a surface percentage of the composite copper layer of, for example, 50-70%.
[0054] It should be noted here that in the above-mentioned embodiment, "the volume percentage of the composite copper layer occupied by the twinned copper grains" can also be expressed as the cross-sectional proportion of the twinned copper grains in the cross-section of the composite copper layer, for example, the cross-sectional proportion or average cross-sectional proportion of the twinned copper grains in one or several cross-sections can be used to express the volume percentage of the composite copper layer occupied by the twinned copper grains.
[0055] Compared with the prior art, the composite copper layer and preparation method thereof of the present invention determines (changes) the starting temperature of grain growth by adjusting the volume percentage of the twin copper grains in the composite copper layer, so that the composite copper layer is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature. The starting temperature of grain growth of the composite copper layer can be effectively controlled according to process requirements, so that the composite copper layer has a relatively stable state before the process is carried out, thereby achieving effective process control and expected process effects.
[0056] The present invention has been described by the above embodiments, however, the above embodiments are for illustrative purposes only and are not intended to be limiting. Those skilled in the art will appreciate that other modifications of the embodiments specifically described herein may be made without departing from the spirit of the present invention. Therefore, the scope of the present invention also encompasses such modifications and is limited only by the scope of the attached patent application documents.
Claims
1. A composite copper layer, characterized in that: The composite copper layer comprises twin copper grains and nano copper grains, wherein the twin copper grains and the nano copper grains are intermixed so that the composite copper layer has a starting temperature. The composite copper layer is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature, wherein the starting temperature of the composite copper layer is determined according to the volume percentage of the twin copper grains occupying the composite copper layer, wherein when the volume percentage of the twin copper grains occupying the composite copper layer is in the range of 1% to 60%, the starting temperature increases with the increase of the volume percentage.
2. The composite copper layer according to claim 1, characterized in that When the volume percentage of the twin copper grains in the composite copper layer is less than 1%, the starting temperature is less than 50 degrees Celsius.
3. The composite copper layer according to claim 1, characterized in that When the volume percentage of the twin copper grains in the composite copper layer is 10-20%, the starting temperature is less than 100 degrees Celsius.
4. The composite copper layer according to claim 1, characterized in that When the volume percentage of the twin copper grains in the composite copper layer is 30-45%, the starting temperature is less than 200 degrees Celsius.
5. The composite copper layer according to claim 1, characterized in that The composite copper layer is applied to a copper-copper metal bonding process.
6. A method for preparing a composite copper layer, characterized in that: Include: A composite copper layer comprising twinned copper grains and nano copper grains is deposited on the surface of the cathode by an electrolytic deposition technique using an electrolyte comprising copper salts, an acid and a water-soluble or alcohol-soluble organic additive. The twinned copper grains and the nano copper grains are intermixed so that the composite copper layer has a starting temperature. The composite copper layer is in a stable state with substantially no grain growth change at a temperature lower than the starting temperature. The starting temperature of the composite copper layer is changed by adjusting the volume percentage of the twinned copper grains occupying the composite copper layer. When the volume percentage of the twinned copper grains occupying the composite copper layer is adjusted to a range of 1% to 60%, the starting temperature increases with an increase in the volume percentage. The electrolysis conditions include a current density of 20~100 mA / cm 2 , the cell voltage is 0.2-3 V, and the distance between the cathode and the anode is 10-300 mm, the acid in the electrolyte is sulfuric acid, hydrochloric acid, phosphoric acid, methanesulfonic acid, sulfonic acid or a mixture thereof, the copper salt contained in the electrolyte is copper sulfate, and the copper sulfate concentration of the electrolyte is above 0.3 mol / L, and the water-soluble or alcohol-soluble organic additive in the electrolyte is a cellulose-based organic additive with a molecular weight of 500-100000 and including cellulose, hemicellulose, carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, methyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, ethyl cellulose, and propyl cellulose.
7. The method for preparing a composite copper layer according to claim 6, characterized in that: The volume percentage of the composite copper layer occupied by the twin copper grains is adjusted by adjusting the content of the water-soluble or alcohol-soluble organic additive.
8. The method for preparing a composite copper layer according to claim 6, characterized in that: When the volume percentage of the twin copper grains in the composite copper layer is adjusted to be less than 1%, the starting temperature is less than 50 degrees Celsius.
9. The method for preparing a composite copper layer according to claim 6, characterized in that: When the volume percentage of the twin copper grains in the composite copper layer is adjusted to 10-20%, the starting temperature is less than 100 degrees Celsius.
10. The method for preparing a composite copper layer according to claim 6, characterized in that: When the volume percentage of the twin copper grains in the composite copper layer is adjusted to 30-45%, the starting temperature is less than 200 degrees Celsius.
